Effect of agomelatine on psychomotor function tests in healthy human volunteers - Sirisha, G.; P., Shovan (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Agomelatine is a melatonergic agonist that acts specifically on MT1/MT2 melatonergic receptors and 5-HT2C antagonism. The present study was taken up to evaluate the effect of Agomelatine 25mg on psychomotor function in healthy human volunteers. Methods: The effect of Agomelatine was studied in 12 healthy volunteers of either gender. The study was a randomised, cross over, placebo controlled study, done after obtaining permission from NIMS Institutional Ethics Committee and informed consent taken from all the subjects, after briefly explaining the study procedure and training them adequately. Psychomotor function was assessed using Choice reaction time (CRT), Critical Flicker fusion test (CFFT), Digit letter substitution test (DLST), Six letter cancellation test (SLCT), Card sorting test (CST) and Visual analog scale (VAS). Psychomotor function tests were performed, 90 minutes after administering Agomelatine 25 mg or placebo. Washout period of seven days was allowed between the cross over. Statistical analysis was done by comparing groups using unpaired t test. Results: There was significant decrease in the mean percentage of time (p<0.01) in CRT in Agomelatine group (20.09±9.47%) when compared to placebo (10.48±3.68%). Improved mean percentage of performance was seen in CFFT with Agomelatine (6.2±2.1%) compared to placebo (9.11±2.99%). No significant difference was noted in the performance of DLST, SLCT and CST. Drug was subjectively rated as sedative on VAS. Conclusions: There is no significant effect of Agomelatine on psychomotor performance. CNS processing of information also improved. Agomelatine can thus be safely administered to depressed patients.